Analisis Tingkat Bahaya Erosi di Sub DAS Simaimai Kabupaten Deli Serdang. - Fanjosafat Sitohang; Kamarlin Pinem (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
This study aims to determine, the erosion hazard that occurs and the level of erosion hazard that occurs in the Simaimai Sub-watershed in Deli Serdang Regency. This research was carried out in 2018 in the Simaimai sub-watershed. The population in this study was all land units in the Simaimai Sub-watershed with a sample of 8 land units taken using the Stratified Random Sampling technique. The data analysis technique used is descriptive qualitative, namely to describe the erosion hazard using the USLE (Universal Soil Loss Equation) method and the erosion hazard level by combining erosion hazard values with erosion hazard level classification criteria. The results showed that: (1) the erosion hazard in the Simaimai sub-watershed was divided into four classes. The most dominant erosion hazard class in Simaimai Sub-watershed is class III, which is in 4 land units. While the most extensive erosion hazard class is the class I erosion hazard found in two land units. The heaviest erosion hazard class (IV) is found in AnLKIV land units. While the smallest erosion hazard class is class II erosion hazard. (2) the level of erosion hazard in the Simaimai watershed includes erosion levels of very light (SR), mild (R), moderate (S), heavy (B) and very heavy (SB).